Hennes & Mauritz (H&M). B : standing up for human rights in China - Derr, Timothy; Raley, Madison; Shea, Caitlin; Siegman, Jackson; O'Rourke, James S., 1946- (London : The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame, 2021)
H&M emphasises their dedication to ethical purchasing while simultaneously expressing a firm long-term commitment to China. By making this declaration, H&M intends to mend its ties with China and reestablish mutual respect and cooperation. How will H&M continue its business links with China if the accusations are true and Xinjiang cotton is irreversibly polluted by forced labour?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social responsibility of business -- Case studies; Business logistics -- Case studies